1999
DOI: 10.1121/1.424683
|View full text |Cite
|
Sign up to set email alerts
|

Intensity discrimination of Gaussian-windowed tones: Indications for the shape of the auditory frequency-time window

Abstract: The just-noticeable difference in intensity jnd(I) was measured for 1-kHz tones with a Gaussian-shaped envelope as a function of their spectro-temporal shape. The stimuli, with constant energy and a constant product of bandwidth and duration, ranged from a long-duration narrow-band "tone" to a short-duration broadband "click." The jnd(I) was measured in three normal-hearing listeners at sensation levels of 0, 10, 20, and 30 dB in 35 dB(A) SPL pink noise. At intermediate sensation levels, jnd(I) depends on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The value of α was chosen according to the study by van Schijndel et al . [50], who used similar Gaussian stimuli to measure spectro-temporal integration. They made the assumption that the auditory system performs a TF analysis through its own TF windows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of α was chosen according to the study by van Schijndel et al . [50], who used similar Gaussian stimuli to measure spectro-temporal integration. They made the assumption that the auditory system performs a TF analysis through its own TF windows.…”
Section: Methodsmentioning
confidence: 99%
“…Gabor atoms have Gaussian shapes in both time and frequency and minimize the TF uncertainty principle [1, 2]. Additionally, it has been suggested that Gaussian-shaped stimuli with an appropriate support in the TF domain excite a limited number of hypothesized TF observation windows of the auditory system compared to broadband and/or long stimuli [50]. Using stimuli with a compact support in the time domain also has the potential advantage to avoid the influence of auditory efferents like the MOCR.…”
Section: Introductionmentioning
confidence: 99%
“…The equivalent rectangular bandwidth of the Gaussian is given by C. The equivalent rectangular duration of the Gaussian equals C À1 . The value of C was chosen based on the study by van Schijndel et al (1999) on intensity discrimination, in which the parameter a of the Gaussian defined above was varied. The goal of the authors was to derive the shape of the "internal" time-frequency observation window of the auditory system.…”
Section: B Stimuli and Apparatusmentioning
confidence: 99%
“…This elementary signal has a Gaussian shape in both domains. Gaussians have been used in a study attempting to measure the shape of the auditory time-frequency window (van Schijndel et al, 1999) and in studies on the effects of spectral and temporal integration in auditory masking (e.g., van den Brink and Houtgast, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…This shape factor was chosen because it defines a signal with the spectral width of a critical band ͑equivalent rectangular bandwidth: 1 4 octave͒ combined with a short duration ͑equivalent rectangular duration: 2.8 ms͒. For low-level stimuli with this particular spectro-temporal shape, listeners are not able to combine stimulus information across multiple frequency channels or across ''multiple looks'' in time ͑van Schijndel et al, 1999͒. The energy of the Gaussian pulse only depends on the amplitude factor A. In its generation, the Gaussian pulse was cut off at 60 dB below the top.…”
Section: A Stimulimentioning
confidence: 99%